Determinants of Adolescents' Desire to Quit Smoking in Indonesia: Data Analysis of the 2014 Global Youth Tobacco Survey - Mega Puspa Sari; Elia Nur Ayunin; Yuli Dwi Setyowati (Universitas Ahmad Dahlan, 2022)
Background: The high prevalence of smoking is not only among adults but also among children and adolescents. Almost all adolescent smokers wish to quit smoking. They are aware of the dangers of cigarettes, tobacco, and other types so they are motivated to quit smoking. This study aims to determine the determinants of the desire to quit smoking in Indonesian students, using a cross-sectional study design. Method: This study is a secondary data analysis of the Global Youth Tobacco Survey (GYTS) in Indonesia in 2014. The sample of the study was all students in grades 7-9 in Indonesia who participated in the 2014 GYTS and had complete data, namely 5,986 people. Logistic regression statistical test analysis was used to determine the relationship between the determinants and the desire to stop smoking in adolescents. Results: Adolescents who want to quit smoking are 92.1%. There is a relationship between adolescents who have tried cigarettes and other types of tobacco on the desire to stop smoking behavior (OR=11,3; 95% CI=5,216-24,615; p<0.025). There is a relationship between the dangers of smoking from family discussions on the behavior and desire of adolescents to stop smoking (OR=2,1; 95% CI=1,213-3,784; p<0.025). Conclusion: Family support and motivation can assist adolescents in reducing smoking habits by monitoring and reminding adolescents of the purpose of quitting smoking, and by inviting adolescents to consult and take therapy with Public Health Services.